1962
DOI: 10.1063/1.1724304
|View full text |Cite
|
Sign up to set email alerts
|

Empty Space Metrics Containing Hypersurface Orthogonal Geodesic Rays

Abstract: In this paper we obtain all empty space metrics which possess hypersurface orthogonal geodesic rays with nonvanishing shear and divergence. By straightforward integration of the Newman-Penrose equations, which are equivalent to the Einstein equations, all solutions are found in closed form and are unique up to a few arbitrary constants. The method of integration is illustrated in detail for the Robinson-Trautman solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 4 publications
0
41
0
Order By: Relevance
“…' g9A 2 P -ee(w) , ImT it =o (5)(6)(7)(8)(9)(10)(11) and the only freedom remaining in the choice of ~ is Then from [4] …”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…' g9A 2 P -ee(w) , ImT it =o (5)(6)(7)(8)(9)(10)(11) and the only freedom remaining in the choice of ~ is Then from [4] …”
Section: -mentioning
confidence: 99%
“…Xt-t X Ali tA ag (3)(4)(5)(6)(7)(8)(9)(10)(11) and we will now show that (3.9) can be used to put X' = 0 while still maintaining the form of G0 . It is clear from (3.10) and ( …”
mentioning
confidence: 99%
“…In the Newman-Penrose formalism this implies that Ψ 0 = κ = 0, that ρ is real and non-zero and σ = 0. In [1] Newman and Tamburino explicitly gave all such metrics and showed that they fall into two classes: the spherical, with ρ 2 = σσ and the cylindrical with ρ 2 = σσ. In [3] I gave a formalism suitable for investigating homothetic symmetries of vacuum solutions of the field equations, and this paper arose from an exercise in applying that formalism to the (algebraically general) spherical Newman-Tamburino solutions, with the purpose of checking that the obvious homothety (see section 2) came out of the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Results up to 1999 are summarized in chapters 26-32 of [10]. Basic papers on certain major classes of such solutions appeared very soon after the present paper: for solutions with geodesic, shearfree and non-twisting rays, Robinson and Trautman [11]; for geodesic twistfree rays, Newman and Tamburino [12]; and for twist and divergence-free rays, Kundt [13] and paper V of this series. Particularly important cases included the NUT solutions [14] and perhaps the most astrophysically important of all exact solutions which can be considered to describe an isolated body, the Kerr solution for a rotating black hole [15].…”
mentioning
confidence: 99%
“…However, reference (12) of this paper is the first of the Mainz series [1] and is therefore now readily available.…”
mentioning
confidence: 99%